건강기능식품 브랜드의 비주얼 아이덴티티 강화를 위한 패키지디자인 제안 -국내 N 브랜드 패키지디자인 제안 사례를 기반으로 - 송지인(Song, Ji In); 유하연(Yoo, Ha Yeon) (기초조형학연구, 2024)
인류에게 ‘건강한 삶’이란 시대를 넘는 꾸준한 관심 키워드이며, 특히 COVID-19 팬데믹 이후 면역력강화에 대한 수요가 급증하면서, 국내 건강기능식품 시장은 최근 5년 동안 빠르게 성장하였다. 국내건강기능식품 시장은 빠르게 변화하는 트렌드와 선두 제품을 모방한 신제품들이 빈번하게 교체되는특징을 보이며, 이는 브랜드의 경쟁력과 장기적 성장을 저해한다. 국내 건강기능식품 N 브랜드는 심미적으로 뛰어난 패키지디자인으로 인정받았으나, 일관된 비주얼 아이덴티티 부재로 장기적인 브랜드충성도와 가치를 확보하지 못하고 있다. 본 연구의 목적은 비주얼 아이덴티티를 강화한 새로운 N 브랜드의 패키지를 제안하고 개선 방향을 도출하여, 차별화된 디자인 전략을 통해 국내 건강기능식품 브랜드의 지속적인 성장을 모색하는 것이다. 이를 위해 국내 건강기능식품의 현황과 패키지디자인의 역할과 중요성을 조사하고, 선행연구를 통해 패키지디자인의 시각적 요소와 체계적 평가 기준을 마련했다. 이를 근거로 비주얼 아이덴티티가 잘 드러난 해외 건강기능식품 5개 브랜드의 패키지디자인을 분석하여 비주얼 아이덴티티 강화 요소를 도출하여 N 브랜드의 새로운 패키지에 적용했다. 제안된 패키지는 평가 기준에 따라 전문가 심층 인터뷰와 질적 분석을 통해 검증되었으며, 최종적으로 건강기능식품 패키지의 비주얼 아이덴티티를 강화할 수 있는 디자인 가이드라인을 제시하였다. 본 연구는 분석사례가 일부 제품군에 한정되고, 모수가 제한된 전문가의 검증에 국한되어 실제 소비자의 의견을 충분히 반영하지 못했다는 한계가 있지만, 국내 건강기능식품 N 브랜드의 비주얼 아이덴티티를 강화할 수있는 패키지디자인 개선안을 제안하고 이를 검증하여, 건강기능식품 패키지디자인 실무에 활용할 수있는 디자인 가이드라인을 제시하였다는 점에 의의가 있다. The concept of healthy living has consistently captured attention across generations. In the wake of the COVID-19 pandemic, there has been a marked increase in demand forimmunity-enhancing products, driving rapid expansion in the Korean health functional food(HFF) market over the last five years. This market is characterized by swiftly evolving trends,with products emulating leading brands quickly entering and exiting the market. N brand, a playerin the domestic HFF sector, has also been introducing visually appealing new products in linewith these trends. However, the lack of a unified visual identity hampers long-term consumerloyalty and brand value growth. This study aims to propose a new packaging design for N brandthat strengthens its visual identity and identifies areas for improvement, seeking sustainablegrowth for domestic HFF brands through distinctive design strategies. To this end, the studyexamines the current landscape of the domestic HFF market and the role and importance ofpackaging design. Key visual elements and systematic evaluation criteria for packaging design areestablished through a review of existing literature. Building on these foundations, the studyanalyzes the packaging designs of five global HFF brands renowned for their strong visualidentities to derive elements that enhance visual identity, which are then applied to the newpackaging for N brand. The proposed packaging is validated through in-depth expert interviewsand qualitative analysis based on the established evaluation criteria. While this study is limitedby its focus on a specific product range and the evaluation being confined to a select group ofexperts, it contributes by proposing a packaging design improvement plan that enhances thevisual identity of N brand and offers design guidelines applicable to the practical field of HFFpackaging design. KCI Citation Count: 0